Evaluation of Strain Elastography for Differentiation of Thyroid Nodules: Results of a Prospective DEGUM Multicenter Study - Friedrich-Rust, M.; Vorlaender, C.; Dietrich, C. F.; Kratzer, W.; Blank, W.; Schuler, A.; Broja, N.; Cui, X. W.; Herrmann, E.; Bojunga, J. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: Many patients with thyroid nodules are presently referred to surgery for not only therapeutic but also diagnostic purposes. The aim of noninvasive diagnostic methods is to optimize the selection of patients for surgery. Strain elastography (SE) enables the ultrasound-based determination of tissue elasticity. The aim of the present study was to evaluate the value of SE for the differentiation of thyroid nodules in a prospective multicenter study.Materials and Methods: The study was registered at clinicaltrials.gov and was approved by the local ethics committees of all participating centers. All patients received an ultrasound (US) of the thyroid gland including color Doppler US. In addition, all nodules were evaluated by SE (Hitachi Medical Systems) using qualitative image interpretation of color distribution (SE-ES), strain value and strain ratio.Results: Overall, 602 patients with 657 thyroid nodules (567 benign, 90 malignant) from 7 centers were included in the final analysis. The sensitivity, specificity, NPV, PPV, +LR were 21 %, 73 %, 86 %, 11 %, 0.8, respectively, for color Doppler US; 69 %, 75 %, 94 %, 30 %, 2.9, respectively, for SE-ES; 56 %, 81 %, 92 %, 32 %, 2.9, respectively, for SE-strain value; and 58 %, 78 %, 92 %, 30 %, 2.6, respectively, for SE-strain ratio. The diagnostic accuracy was 71 % for both strain value and strain ratio of nodules.Conclusion: SE as an additional ultrasound tool improves the value of ultrasound for the work-up of thyroid nodules. It might reduce diagnostic surgery of thyroid nodules in the future.
Keywords: elastography; thyroid; strain elastography